Uji Kepraktisan Media Infografis terhadap Peningkatan Pendidikan Karakter berdasarkan Program “G7KAIH” pada SMPN 4 SATAP MALANGKE: Penelitian - Ramli, Nuranisa; Erwana, Erwana; Khumaerah, St; H, Nurhikmah; Ishak, Suryadi; Safaruddin, Safaruddin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the practicality of the G7KAIH character-value–based infographic media in enhancing character education among students at SMPN 4 SATAP Malangke. The research employed a Research and Development (R&D) design using the ADDIE model, focusing on the implementation and evaluation stages through practicality testing by teachers and students. The instruments used were teacher and student practicality questionnaires. The results show that the infographic media obtained a practicality score of 90% (very practical) based on teacher responses, 80% (practical) from the small group test, and 83% (very practical) from the large group test. These findings indicate that the G7KAIH infographic media is easy to use, visually appealing, relevant to the content, and effective in supporting character education. Therefore, this media is feasible to be used as a character learning tool for junior high school students.